Revision of the genus Afrosmicronyx Hustache (Coleoptera, Curculionidae, Curculioninae) - Haran, Julien; Perrin, Hélène (Zootaxa, 2017)
The species of the Afrotropical genus Afrosmicronyx Hustache (Curculionidae, Curculioninae, Smicronychini), biocontrol agents of parasitic plants in crops (Striga, Orobanchaceae), are revised. Ten species are recognized, two of them described as new (A. mirei Haran, sp. n. and A. madagascariensis Haran, sp. n.). A key to the species with photographs of the habitus and male genitalia of type specimens is provided.